Plastome structure, phylogenomic analyses and molecular dating of Arecaceae - Chen, Da-Juan; Landis, Jacob B.; Wang, Hong-Xin; Sun, Qing-Hui; Wang, Qiao; Wang, Hua-Feng (Frontiers in Plant Science, 2022)
Arecaceae is a species-rich clade of Arecales, while also being regarded as a morphologically diverse angiosperm family with numerous species having significant economic, medicinal, and ornamental value. Although in-depth studies focused on the chloroplast structure of Arecaceae, as well as inferring phylogenetic relationships using gene fragments, have been reported in recent years, a comprehensive analysis of the chloroplast structure of Arecaceae is still needed. Here we perform a comprehensive analysis of the structural features of the chloroplast genome of Arecaceae, compare the variability of gene sequences, infer phylogenetic relationships, estimate species divergence times, and reconstruct ancestral morphological traits. In this study, 74 chloroplast genomes of Arecaceae were obtained, covering five subfamilies. The results show that all chloroplast genomes possess a typical tetrad structure ranging in size between 153,806-160,122 bp, with a total of 130-137 genes, including 76-82 protein-coding genes, 29-32 tRNA genes, and 4 rRNA genes. Additionally, the total GC content was between 36.9-37.7%. Analysis of the SC/IR boundary indicated that the IR region underwent expansion or contraction. Phylogenetic relationships indicate that all five subfamilies in Arecaceae are monophyletic and that Ceroxyloideae and Arecoideae are sister groups (BS/PP = 100/1). The results of molecular dating indicate that the age of the crown group of Arecaceae is likely to be 96.60 [84.90-107.60] Ma, while the age of the stem group is 102.40 [93.44-111.17] Ma. Reconstruction of ancestral traits indicate that the ancestral characteristics of the family include monoecious plants, one seed, six stamens, and a smooth pericarp.